Antibacterial, antioxidant, and SucAla3-based anti-aging activities of Johar flower extract (Cassia siamea Lamk.) - Hasballah, Kartini; Murniana , Murniana; Diah, Muhammad; Rusly, Renzavaldy; Fadlia, Yosi; Amna, Usratul; Husni, Muhammad NRR. (Narra X, 2025)
Cassia siamea flowers are recognized for their diverse secondary metabolites, including flavonoids, triterpenoids, and steroids, which have been linked to various therapeutic properties. Although previous studies have primarily focused on the pharmacological activities of C. siamea leaves, bark, or crude extracts, evidence regarding the bioactivity of its flower extracts—particularly those obtained through sequential solvent partitioning—remains limited. The aim of this study was to investigate the antibacterial, antioxidant, and anti-aging potential of C. siamea flower extracts obtained through sequential solvent extraction. The extracts were prepared by maceration with methanol, followed by partitioning with n-hexane and ethyl acetate. Antibacterial activity was assessed using the agar well diffusion method against Staphylococcus aureus and Escherichia coli. Antioxidant activity was determined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Anti-aging properties were evaluated through elastase inhibition assays, with the reduction of SucAla3 formation used as an indicator. Phytochemical profiling of the extracts was conducted using chromatography–mass spectrometry (GC–MS). The findings revealed that the ethyl acetate extract exhibited the highest antibacterial activity, with inhibition zones of 8.08±0.84 mm and 7.38±0.33 mm against S. aureus and E. coli, respectively. Antioxidant analysis showed the methanol extract to be the most effective (IC50=66.76 µg/mL), followed by the methanol partition (IC50=75.97 µg/mL). The methanol extract demonstrated significant elastase inhibition, achieving 97.53% activity (IC50=13.89 µg/mL). GC–MS analysis identified two compounds as the major phytocomponents of the methanolic extract, namely octadecanoic acid, 2-(2-hydroxyethoxy)ethyl ester and tetradecanoic acid. In conclusion, C. siamea flower extracts have therapeutic potentials, particularly as antibacterial, antioxidant, and anti-aging agents.